Translation and validation of two disease-specific patient-reported outcome measures (Bladder Cancer Index and FACT-Bl-Cys) in Dutch bladder cancer patients - Charlotte T. J. Michels; Carl J. Wijburg; Inger L. Abma; J. Alfred Witjes; Janneke P. C. Grutters; Maroeska M. Rovers (SpringerOpen, 2019)
Abstract Background The Bladder Cancer Index (BCI) and Functional Assessment of Cancer Therapy-Bladder-Cystectomy (FACT-Bl-Cys) were developed to measure disease-specific health-related quality of life (HRQOL) in bladder cancer patients and patients treated with radical cystectomy, respectively. Both patient-reported outcome measures (PROMs) are frequently used in clinical practice, but are not yet validated according to the COSMIN criteria and not yet available in Dutch. Therefore, the aim of this study was to translate the BCI and FACT-Bl-Cys into Dutch and to evaluate their measurement properties according to the COSMIN criteria. Methods The BCI and FACT-Bl-Cys were translated into Dutch using a forward-backward method, and subsequently administered at baseline (pre-operatively) and 3 months post-operatively in bladder cancer patients who received a radical cystectomy. Validity (content and construct), reliability (internal consistency, test-retest reliability, and measurement error), floor and ceiling effects, and responsiveness were assessed according to the COSMIN criteria. Results Forward-backward translation encountered no particular linguistic problems. In total 260 patients completed the baseline measurement, while 182 patients completed the three-month measurement. Only a ceiling effect was identified for the BCI. Hypotheses testing for construct validity was satisfying, as 67% and 92% of the hypothesized correlations were confirmed. Structural validity was moderate for both measures, as confirmatory factor analyses showed limited fit. Reliability of both PROMs was good. The intraclass correlation coefficient (ICC) of the BCI domains ranged from 0.47 to 0.93, minimal value of Cronbach's α was 0.70, smallest detectable change on group level (SDC group) ranged from 1.9 to 8.6. The ICC of the FACT-Bl-Cys domains ranged from 0.43 to 0.83, minimal value of Cronbach's α was 0.77, SDC group was around 1. Only the FACT-Bl-Cys total score was found to be responsive to changes in generic quality of life. Conclusions The Dutch versions of the BCI and FACT-Bl-Cys were shown to be reliable and have good content validity. Structural validity was limited for both measures. Only the FACT-Bl-Cys total score was responsive to changes in generic HRQOL. Despite some limitations, both PROMs seem suitable for use in clinical practice and research.